The German specialist lexicon. - Weske-Heck, Gesa (American Medical Informatics Association, 2002)
The German language and in particular biomedical terms exhibit a rich and productive morphology. Beyond inflection and comparison forms frequently spelling variants, German - Greek/Latin synonyms and nominal compounds exist. For the English language, the SPECIALIST LEXICON, part of the UMLS project, covers a broad range of biomedical terms. In this paper we describe the database model and the functionality of the GERMAN SPECIALIST LEXICON, an ongoing project to develop a lexical resource for German-language medical terminology. Similar to the SPECIALIST LEXICON it is accompanied by tools for the recognition and generation of lexical variants, as well as by databases linking synonymous words, spelling variants, phrases and abbreviations.